PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN DI PT WAHANATRI TATA WICAKSANA - Fauziyyah Wulansari, Sadira; Tilova, Nurdinni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of job training and career development on employee performance at PT. Wahanatri Tata Wicaksana both partially and simultaneously. This type of research uses the sampling method. The total population was 106 with data collection techniques through observation and questionnaires, and the sample obtained in this study was 82 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that job training has a significant effect on employee performance. By hypothesis testing, it is obtained that tcount > t table or tcount > ttable or (14.456 > 1.989) thus H0 is rejected and H1 is accepted, the regression equation Y = 6.486 + 0.850X1, the correlation value is 0.850 This means that the two variables have a strong level of relationship and the coefficient of determination is 85.0%. Career development has a significant effect on employee work productivity. By hypothesis testing, tcount > t table or (11,321 > 1.989), thus H0 is rejected and H2 is accepted. The regression equation Y = 141.321 + 0.710X2, the correlation value is 0.785, meaning that the two variables have a strong level of relationship with a coefficient of determination of 78.5%. Job training and career development simultaneously have a significant effect on employee performance. By hypothesis testing, the calculated F value > F table or (115.822 > 3.108) is obtained, thus H0 is rejected and H3 is accepted. The regression equation Y = 8.418 + 0.099X1 + 0.704X2, the correlation value is 0.785, meaning that the independent variable and the dependent variable have a strong level of relationship. The coefficient of determination value is 78.5% while the remaining 21.5% is influenced by other factors.